2009
DOI: 10.4314/ajfand.v9i6.46268
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of children (6-59 months) among HIV-positive mothers/caregivers living in an urban setting of Uganda.

Abstract: Few studies have attempted to establish the burden of childhood malnutrition and the associated factors among households of HIV-positive mothers/caregivers particularly in urban settings. There is also no satisfactory evidence of health and nutritional benefits of food aid in this particular group where options to attain a balanced diet are generally minimal. A cross-sectional survey was therefore organized to assess the prevalence of malnutrition and establish the contributory factors that would be vital in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
(15 reference statements)
0
7
0
1
Order By: Relevance
“…Complementary feeding initiation at recommended age (6 months) and better dietary diversity scores (≥4) were also associated with reduced odds of stunting. A study from Uganda showed that low dietary diversity was a predictor of stunting [29]. A study done in Sidama zone reported that dietary inadequacy and low diet quality in terms of diversified diet and availability of micronutrients had a significant negative association with child growth [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementary feeding initiation at recommended age (6 months) and better dietary diversity scores (≥4) were also associated with reduced odds of stunting. A study from Uganda showed that low dietary diversity was a predictor of stunting [29]. A study done in Sidama zone reported that dietary inadequacy and low diet quality in terms of diversified diet and availability of micronutrients had a significant negative association with child growth [30].…”
Section: Discussionmentioning
confidence: 99%
“…A study done in Zambia showed no significant association between maternal education status and stunting and underweight whereas wasting prevalence did have a significant association with maternal education in which wasting prevalence were minimal in households with educated mothers [31]. On the other hand, a study done in Nigeria and Uganda showed that there was a positive association between levels of maternal education and nutritional indices [29, 32]. A study from Jimma in Ethiopia reported no statistically significant association between child nutritional status and education status [33].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Bangladesh indicated that children of mothers with low BMI, mothers having less antenatal check-ups and rural mothers had significantly lower minimum dietary diversity rate, which are not a statistically significant factors in our findings [ 28 ]. A study from Uganda showed that consumption of a diversified diet was significantly associated with socio-economic status [ 31 ]. Similarly, a study in Indonesia also showed that mother’s education, rural residence and lower category of infants' age were negatively associated with minimum dietary diversity and minimum meal frequency [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, majority (67.6%) of HIV exposed children have complemented with grains in the last 24 hours preceding the survey which is consistent with the current EDHS report [ 30 ]. A study conducted in Uganda reported that 88% of households with HIV positive mothers reportedly consumed mainly cereals in the 24 hours prior to the assessment [ 31 ]. A study from Bangladesh reported that about 85% of children aged 6–23 months were given grains [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sebuah studi di Uganda menyebutkan anak yang mendapatkan keragaman makanan yang rendah menjadi salah satu faktor penyebab stunting. Di sisi lain, beberapa alasan yang menyebabkan tidak tercapainya keragaman makanan yang optimal adalah faktor status sosial ekonomi keluarga dan akses memeroleh makanan (28). Skor keragaman makanan menjadi faktor yang memiliki hubungan signifikan dengan nilai Z˗score PB/U yang rendah pada anak di Ethiopia (29).…”
Section: Pembahasanunclassified